Preparation method of high-strength ceramic fiber

By using polycarbosilane and reinforcement, the problem of structural changes in ceramic fibers under high temperature and external impact is solved, the high strength and self-repair performance of ceramic fibers are achieved, and the reliability and safety of components are improved. .

CN119465446APending Publication Date: 2025-02-18吉祥三宝高科新材料有限公司

Patent Information

Application Number
CN202411619449.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Ceramic fibers prepared by the prior art tend to cause microstructure changes under high temperature and external impact, destroy the integrity and continuity of the material, reduce their strength, and lack self-repairing properties.

Method used

High-strength ceramic fibers are prepared by melt spinning using the substance added by polycarbosilane and the enhancer hydrogen silicon as raw materials. The enhancer contains imino groups, disulfide bonds, ester groups, and carbon-carbon double bonds. These functional groups form a tight crosslinking network to improve the density and uniformity of the fiber, thereby enhancing its strength and having self-healing properties.

Benefits of technology

The prepared high-strength ceramic fiber has excellent self-repair effect and improved mechanical properties. It can automatically repair and restore the original strength and performance when minor damage is encountered, improving the reliability and safety of the entire component.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength ceramic fiber, and belongs to the technical field of ceramic fibers.The preparation method comprises the following steps that polycarbosilane is added into anhydrous xylene and dissolved at the temperature of 160-200 DEG C, then a reinforcing agent is added, a reaction is conducted for 8-24 h at the temperature of 160-200 DEG C, cooling, atmospheric distillation and reduced pressure distillation are conducted, and modified polycarbosilane is obtained; placing the modified polycarbosilane in a melt spinning cylinder, slowly heating the modified polycarbosilane to a molten state in an inert atmosphere, and carrying out defoaming treatment; then pressurizing to 3MPa, and enabling the melt to flow out through a filter screen and a spinneret plate to obtain a silicon carbide fiber bundle; and putting the silicon carbide fiber bundles into a sintering furnace, introducing nitrogen, heating, and cooling along with the furnace to obtain the high-strength ceramic fiber. The ceramic fiber prepared by the invention has excellent self-repairing performance and mechanical property, and is suitable for numerous application scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic fibers, and in particular relates to a method for preparing high-strength ceramic fibers. Background Art

[0002] As an excellent thermal insulation material, ceramic fiber has the advantages of high temperature resistance, good stability, low thermal conductivity and mechanical vibration resistance. In addition, it has excellent toughness and fire resistance and is widely used. Ceramic fiber can be divided into oxide ceramic fiber and non-oxide ceramic fiber according to chemical composition. Among them, silicon carbide fiber in non-oxide ceramic fiber has high thermal conductivity, high strength and creep resistance, and is usually used as a raw material for preparing high-strength ceramic fiber.

[0003] Carbon nanotubes (CNTs) are a new type of nanomaterial with excellent mechanical, electrical and thermal properties. The tensile strength of carbon nanotubes can reach 50-200Gpa, and the elastic modulus can reach 1Tpa, which is equivalent to the modulus of diamond. At the same time, it also has ultra-high elasticity, toughness (theoretical maximum elongation is 20%) and fatigue resistance, making it the most ideal reinforcement material for high-performance fibers. If carbon nanotubes can be evenly wrapped inside silicon carbide, it can effectively exert the excellent mechanical, electrical and dielectric properties of carbon nanotubes, and can also take advantage of the corrosion resistance and high temperature oxidation resistance of silicon carbide, while overcoming the brittleness of silicon carbide fibers, and thus obtain flexible, conductive and wave-absorbing ceramic fibers.

[0004] The patent with the patent announcement number CN106930004B discloses a method for preparing flexible silicon carbide / carbon nanotube composite fiber membrane by electrospinning. The patent adds silicon carbide precursor (polycarbosilane PCS) and easy-to-spin polymer into an organic solvent and stirs for a period of time, then adds carbon nanotubes for ultrasonic dispersion to obtain a polycarbosilane / carbon nanotube mixed spinning solution, and electrospins the solution to obtain a polycarbosilane / carbon nanotube composite fiber membrane; the polycarbosilane / carbon nanotube composite fiber membrane is subjected to an infusible treatment and a high-temperature pyrolysis treatment to obtain a flexible silicon carbide / carbon nanotube composite fiber membrane, which improves the mechanical properties of the silicon carbide / carbon nanotube composite fiber membrane and has good application prospects in the fields of high-temperature sensors and composite material reinforcement. However, the ceramic fibers prepared by this patent and the prior art are used in many fields. For example, in the aerospace field, ceramic fibers are often used to manufacture high-temperature components. These components may be subjected to various external impacts and high-temperature environments during flight. These damages will cause changes in the microstructure of the ceramic fibers, such as grain growth and crack expansion, thereby destroying the integrity and continuity of the material and reducing its strength. If ceramic fibers with self-healing properties can be prepared, when the material is slightly damaged, it can automatically repair and restore its original strength and performance, thereby improving the reliability and safety of the entire component. Summary of the invention

[0005] In order to solve the disadvantage that the ceramic fiber prepared by the prior art in the background art does not have self-repairing properties, the purpose of the present invention is to provide a method for preparing high-strength ceramic fiber.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A method for preparing high-strength ceramic fiber comprises the following steps:

[0008] S1: Add polycarbosilane to anhydrous xylene and dissolve it at 160-200°C, then add a reinforcing agent, react at 160-200°C for 8-24 hours, cool, and distill at normal pressure and reduced pressure to obtain modified polycarbosilane. The reinforcing agent is made by condensation reaction of self-repairing monomers and aldehyde-modified multi-walled carbon nanotubes, and contains an imino group, a disulfide bond, an ester group, and a carbon-carbon double bond.

[0009] The dosage ratio of polycarbosilane, anhydrous xylene and reinforcing agent is 100g:150mL:0.2-0.6g.

[0010] In the above steps, the reinforcing agent containing carbon-carbon double bonds can undergo a silylation reaction with the silicon-hydrogen bonds in polycarbosilane, so that the reinforcing agent and polycarbosilane can form a tighter cross-linked network. The defects and voids inside the ceramic fiber prepared from this raw material will be reduced, thereby improving the density and uniformity of the fiber. The improvement in density and uniformity can further enhance the strength of the fiber.

[0011] S2: placing the modified polycarbosilane in a melt spinning cylinder, slowly heating it to a molten state under an inert atmosphere, and performing a degassing treatment; then pressurizing it to 3 MPa, and the melt flows through a filter screen and a spinneret to obtain a silicon carbide fiber bundle;

[0012] S3: placing the silicon carbide fiber bundle in a sintering furnace, passing nitrogen, heating and heating, and obtaining high-strength ceramic fibers after cooling in the furnace.

[0013] Furthermore, in step S1, the specific steps of atmospheric distillation and reduced pressure distillation are atmospheric distillation at 170-200° C. under nitrogen atmosphere protection until no distillate is precipitated, and reduced pressure distillation at 300-350° C. until no distillate is precipitated.

[0014] Furthermore, in step S2, the inert gas is one of nitrogen or argon.

[0015] Further, in step S3, the temperature is increased to 500-550°C at a rate of 100-200°C / h, and kept at this temperature for 2-4h; then the temperature is increased to 1000°C at a rate of 100-200°C / h, and kept at this temperature for 4-6h; then the temperature is increased to 1300°C at a rate of 500-600°C / h, and kept at this temperature for 0.5-1h, and then cooled with the furnace; the flow rate of nitrogen is 100-200mL / min.

[0016] Furthermore, the preparation method of the enhancer is:

[0017] Add the self-repairing monomer and the aldehyde-modified multi-walled carbon nanotubes into anhydrous ethanol, react at 20-30° C. for 20-30 minutes, filter, and dry to obtain an enhancer;

[0018] The usage ratio of the self-repairing monomer, the aldehyde-modified multi-walled carbon nanotubes and the anhydrous ethanol is 3-6 g: 160 g: 1-1.2 L.

[0019] In the above steps, the amino group in the self-repairing monomer can undergo a condensation reaction with the aldehyde group on the surface of the aldehyde-modified multi-walled carbon nanotube to generate an imine bond, thereby obtaining an enhancer containing an imine group, a disulfide bond, an ester group, and a carbon-carbon double bond. The imine bond is a dynamic covalent carbon-nitrogen double bond that is reversible at room temperature. The self-repair process of the imine bond is a dynamic equilibrium process. Within the material, the breaking and recombination of the imine bond are constantly carried out, so that the material can self-repair to a certain extent and maintain its integrity and performance.

[0020] Furthermore, the preparation method of the self-repairing monomer is:

[0021] Add cystine, propylene alcohol, p-toluenesulfonic acid and toluene into a reaction bottle and stir; heat to 112°C, keep reflux for 3 hours, cool to -5 to 5°C in a water bath, keep warm for 1 hour; filter, wash with frozen toluene, and dry to obtain a self-repairing monomer;

[0022] The dosage ratio of cystine, allyl alcohol, p-toluenesulfonic acid and toluene is 24g:14mL:2-4g:500-700mL.

[0023] In the above steps, the carboxyl group of cysteine ​​and the hydroxyl group of allyl alcohol undergo esterification reaction to obtain a self-repairing monomer, which contains a disulfide bond, an amino group, an ester group, and a carbon-carbon double bond. The bond energy of the disulfide bond is low, and it can break or undergo a reversible reaction under external stimuli such as light and heat, and has self-repairing properties.

[0024] Furthermore, the preparation method of aldehyde-modified multi-walled carbon nanotubes is as follows:

[0025] The aminated multi-walled carbon nanotubes are added into a dialdehyde aqueous solution, stirred at room temperature for 6-8 hours, washed with deionized water, centrifuged and dried to obtain the aldehyde-aminated carbon nanotubes.

[0026] The molar ratio of the amino-modified multi-walled carbon nanotubes to the dialdehyde is 1-3:1.

[0027] Furthermore, the dialdehyde is any one of glutaraldehyde and hexanedialdehyde.

[0028] Beneficial effects of the present invention:

[0029] 1. The present invention uses the substance obtained by silane hydroaddition of polycarbosilane and a reinforcing agent as a raw material, and prepares high-strength ceramic fibers by melt spinning. The reinforcing agent contains an imino group, a disulfide bond, an ester group, and a carbon-carbon double bond, wherein the imino group and the disulfide bond have self-repairing properties, and the ceramic fiber prepared by the reinforcing agent has an excellent self-repairing effect; the ester group, as an organic functional group, has a certain volume, and will improve the dispersibility of the reinforcing agent through a steric hindrance effect, thereby improving the strength of the ceramic fiber; the reinforcing agent containing a carbon-carbon double bond can undergo a silane hydroaddition reaction with the silicon-hydrogen bond in the polycarbosilane, so that the reinforcing agent and the polycarbosilane can form a tighter cross-linked network, which will help reduce defects and voids inside the ceramic fiber, thereby improving the density and uniformity of the fiber. The improvement in density and uniformity can further enhance the strength of the fiber.

[0030] 2. The present invention prepares high-strength ceramic fibers with the best comprehensive performance by strictly controlling the amount of reinforcing agent. When too little reinforcing agent is added, it is difficult to form an effective network structure, resulting in reduced strength of the material. When too little reinforcing agent is added, the repair sites become sparse, resulting in the ceramic fiber being unable to trigger the self-repair mechanism in a timely and effective manner when damaged. When too much reinforcing agent is added, the dispersibility of the reinforcing agent in the raw material becomes poor, and it is difficult to form an effective network structure, thereby affecting the strength of the ceramic fiber. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The amino carbon nanotubes in the present invention are purchased from Xianfeng Nanomaterial Technology Co., Ltd., with the serial number XFM62, a length of 50 μm, a diameter of 8-15 nm, a purity of >97.0 wt%, an amino content of >0.45 wt%, and a type of multi-walled carbon nanotubes.

[0033] Preparation Example 1

[0034] The preparation method of the self-repairing monomer of this preparation example is:

[0035] Add 24 g of cystine, 14 mL of propylene alcohol, 2 g of p-toluenesulfonic acid, and 500 mL of toluene into a reaction bottle and stir; heat to 112° C., keep reflux for 3 h, cool to 5° C. in a water bath, and keep warm for 1 h; filter, wash with frozen toluene, and dry to obtain a self-healing monomer.

[0036] Preparation Example 2

[0037] The preparation method of the self-repairing monomer of this preparation example is:

[0038] Add 24 g of cystine, 14 mL of propylene alcohol, 3 g of p-toluenesulfonic acid, and 600 mL of toluene into a reaction bottle and stir; heat to 112° C., keep reflux for 3 h, cool to -5° C. in a water bath, and keep warm for 1 h; filter, wash with frozen toluene, and dry to obtain a self-healing monomer.

[0039] Preparation Example 3

[0040] The preparation method of the self-repairing monomer of this preparation example is:

[0041] Add 24 g of cystine, 14 mL of propylene alcohol, 4 g of p-toluenesulfonic acid, and 700 mL of toluene into a reaction bottle and stir; heat to 112° C., keep reflux for 3 h, cool to 0° C. in a water bath, and keep warm for 1 h; filter, wash with frozen toluene, and dry to obtain a self-healing monomer.

[0042] Preparation Example 4

[0043] The preparation method of the self-repairing monomer of this preparation example is:

[0044] Add 24 g of cystine, 15 mL of propanol, 2 g of p-toluenesulfonic acid, and 500 mL of toluene into a reaction bottle and stir; heat to 112° C., keep reflux for 3 h, cool to 5° C. in a water bath, and keep warm for 1 h; filter, wash with frozen toluene, and dry to obtain a self-repairing monomer.

[0045] Preparation Example 5

[0046] The self-repairing monomer in this preparation example is 24 g of cystine.

[0047] Preparation Example 6

[0048] The preparation method of the enhancer of this preparation example is:

[0049] 3 g of the self-repairing monomer prepared in Preparation Example 1 and 160 g of aldehyde-modified multi-walled carbon nanotubes were added to 1.2 L of anhydrous ethanol, reacted at 20° C. for 20 min, filtered, and dried to obtain an enhancer;

[0050] The preparation method of aldehyde-modified multi-walled carbon nanotubes is as follows:

[0051] 0.61 mL of adipaldehyde (0.005 mol) was dissolved in 100 mL of water, and then 0.06 g of amino-modified multi-walled carbon nanotubes (0.005 mol) was added to the adipaldehyde aqueous solution, and the mixture was stirred for reaction at room temperature for 6 hours. After the reaction, the mixture was washed with deionized water, centrifuged, and dried to obtain the aldehyde-modified multi-walled carbon nanotubes.

[0052] Preparation Example 7

[0053] The preparation method of the enhancer of this preparation example is:

[0054] 4.5 g of the self-healing monomer prepared in Preparation Example 2 and 160 g of aldehyde-modified multi-walled carbon nanotubes were added to 1.1 L of anhydrous ethanol, reacted at 25° C. for 25 min, filtered, and dried to obtain an enhancer;

[0055] The preparation method of aldehyde-modified multi-walled carbon nanotubes is as follows:

[0056] Dissolve 1 mL of 50% glutaraldehyde (0.005 mol) in 100 mL of water, then add 0.12 g of amino-modified multi-walled carbon nanotubes (0.010 mol) into the glutaraldehyde aqueous solution, stir and react at room temperature for 7 hours, wash with deionized water after the reaction, centrifuge and dry to obtain the aldehyde-modified multi-walled carbon nanotubes.

[0057] Preparation Example 8

[0058] The preparation method of the enhancer of this preparation example is:

[0059] 6 g of the self-repairing monomer prepared in Preparation Example 3 and 160 g of aldehyde-modified multi-walled carbon nanotubes were added to 1 L of anhydrous ethanol, reacted at 30° C. for 30 min, filtered, and dried to obtain an enhancer;

[0060] The preparation method of aldehyde-modified multi-walled carbon nanotubes is as follows:

[0061] 1 mL of 50% glutaraldehyde (0.005 mol) was dissolved in 100 mL of water, and then 0.18 g of amino multi-walled carbon nanotubes (0.015 mol) was added to the glutaraldehyde aqueous solution, and the mixture was stirred for reaction at room temperature for 8 hours. After the reaction, the mixture was washed with deionized water, centrifuged, and dried to obtain the aldehyde-modified multi-walled carbon nanotubes.

[0062] Preparation Example 9

[0063] This preparation example provides an enhancer, which is different from Preparation Example 6 in that the self-healing monomer in Preparation Example 6 is replaced by the product prepared in Preparation Example 4.

[0064] Preparation Example 10

[0065] This preparation example provides an enhancer, which is different from Preparation Example 6 in that the self-repairing monomer in Preparation Example 6 is replaced by the product prepared in Preparation Example 5.

[0066] Preparation Example 11

[0067] The reinforcing agent in this preparation example is aldehyde-modified multi-walled carbon nanotubes, and the preparation method of aldehyde-modified multi-walled carbon nanotubes is as follows:

[0068] 0.61 mL of adipaldehyde (0.005 mol) was dissolved in 100 mL of water, and then 0.06 g of amino-modified multi-walled carbon nanotubes (0.005 mol) was added to the adipaldehyde aqueous solution, and the mixture was stirred for reaction at room temperature for 6 hours. After the reaction, the mixture was washed with deionized water, centrifuged, and dried to obtain the aldehyde-modified multi-walled carbon nanotubes.

[0069] Example 1

[0070] S1: Add 100g polycarbosilane to 150mL anhydrous xylene, dissolve at 160℃, then add 0.05g enhancer, react at 160℃ for 8h, cool, and distill under normal pressure and vacuum to obtain modified polycarbosilane. The specific steps of normal pressure distillation and vacuum distillation are: distill at 170℃ under nitrogen atmosphere until no distillation is precipitated, and distill under vacuum at 300℃ until no distillation is precipitated. ;

[0071] S2: placing the modified polycarbosilane on a melt spinning cylinder, slowly heating it to a molten state under nitrogen, and performing a degassing treatment; then pressurizing it to 3 MPa, and the melt flows through a filter screen and a spinneret to obtain a silicon carbide fiber bundle;

[0072] S3: Place the silicon carbide fiber bundle in a sintering furnace, pass nitrogen, heat and heat up, and obtain high-strength ceramic fiber after cooling with the furnace; heat and heat up to 500°C at a rate of 100°C / h, and keep warm for 2h; then heat up to 1000°C at a rate of 100°C / h, and keep warm for 4h; then heat up to 1300°C at a rate of 500°C / h, keep warm for 0.5h, and cool with the furnace; wherein the flow rate of nitrogen is 100mL / min.

[0073] The preparation method of the enhancer is the same as that of Preparation Example 6.

[0074] Example 2

[0075] S1: Add 100g polycarbosilane to 150mL anhydrous xylene, dissolve at 180℃, then add 0.4g enhancer, react at 160℃ for 16h, cool, and distill under normal pressure and vacuum to obtain modified polycarbosilane. The specific steps of normal pressure distillation and vacuum distillation are: distill at 180℃ under nitrogen atmosphere until no distillation is precipitated, and distill under vacuum at 325℃ until no distillation is precipitated. ;

[0076] S2: placing the modified polycarbosilane on a melt spinning cylinder, slowly heating it to a molten state under nitrogen, and performing a degassing treatment; then pressurizing it to 3 MPa, and the melt flows through a filter screen and a spinneret to obtain a silicon carbide fiber bundle;

[0077] S3: Place the silicon carbide fiber bundle in a sintering furnace, pass nitrogen, heat and heat up, and cool with the furnace to obtain high-strength ceramic fiber; heat and heat up to 525°C at a rate of 150°C / h, and keep warm for 3 hours; then heat up to 1000°C at a rate of 150°C / h, and keep warm for 5 hours; then heat up to 1300°C at a rate of 550°C / h, keep warm for 0.75 hours, and cool with the furnace; wherein the flow rate of nitrogen is 150mL / min.

[0078] The preparation method of the enhancer is the same as that of Preparation Example 7.

[0079] Example 3

[0080] S1: Add 100g polycarbosilane to 150mL anhydrous xylene, dissolve at 200℃, then add 0.6g enhancer, react at 200℃ for 24h, cool, and distill under normal pressure and vacuum to obtain modified polycarbosilane. The specific steps of normal pressure distillation and vacuum distillation are: distill at 200℃ under nitrogen atmosphere until no distillation is precipitated, and distill at 350℃ under vacuum until no distillation is precipitated. ;

[0081] S2: placing the modified polycarbosilane on a melt spinning cylinder, slowly heating it to a molten state under nitrogen, and performing a degassing treatment; then pressurizing it to 3 MPa, and the melt flows through a filter screen and a spinneret to obtain a silicon carbide fiber bundle;

[0082] S3: Place the silicon carbide fiber bundle in a sintering furnace, heat it with argon, and obtain high-strength ceramic fiber after cooling in the furnace; heat it to 550°C at a rate of 200°C / h and keep it warm for 4 hours; then heat it to 1000°C at a rate of 200°C / h and keep it warm for 6 hours; then heat it to 1300°C at a rate of 600°C / h, keep it warm for 1 hour, and cool in the furnace; wherein the flow rate of nitrogen is 200mL / min.

[0083] The preparation method of the enhancer is the same as that of Preparation Example 8.

[0084] Comparative Example 1

[0085] A method for preparing high-strength ceramic fiber, compared with Example 1, the difference is that the reinforcing agent in Example 1 is replaced by the product prepared in Preparation Example 9, and the other raw materials, processes and parameters are the same as Example 1.

[0086] Comparative Example 2

[0087] A method for preparing high-strength ceramic fiber, compared with Example 1, the difference is that the reinforcing agent in Example 1 is replaced by the product prepared in Preparation Example 10, and the other raw materials, processes and parameters are the same as Example 1.

[0088] Comparative Example 3

[0089] A method for preparing high-strength ceramic fiber, compared with Example 1, the difference is that the reinforcing agent in Example 1 is replaced by the product prepared in Preparation Example 11, and the other raw materials, processes and parameters are the same as Example 1.

[0090] Comparative Example 4

[0091] A method for preparing high-strength ceramic fiber, compared with Example 1, the difference is that the "0.2g reinforcing agent" in Example 1 is replaced by "0.1g reinforcing agent", and the remaining raw materials, processes and parameters are the same as Example 1.

[0092] Comparative Example 5

[0093] A method for preparing high-strength ceramic fiber, compared with Example 3, the difference is that the "0.6g reinforcing agent" in Example 3 is replaced by "0.7g reinforcing agent", and the remaining raw materials, processes and parameters are the same as Example 3.

[0094] The performance of the ceramic fibers prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was tested, and the test results are shown in Table 1:

[0095] 1. Tensile strength test: The tensile strength of the ceramic fibers prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was tested using a YG-002 single fiber electronic strength tester.

[0096] 2. Self-healing performance test: Use a knife to make a 3 mm scratch on the surface of the ceramic fiber prepared in Examples 1 to 3 and Comparative Examples 1 to 5, place it under 80% humidity and 100°C for 24 hours, measure the tensile strength at break before and after self-healing, and calculate the self-healing rate. Self-healing rate (%) = tensile strength of the composite material before treatment / tensile strength of the composite material after treatment × 100%.

[0097] Table 1

[0098] project Tensile strength / Gpa Self-repair rate / % Example 1 1.92 86.9 Example 2 2.19 88.4 Example 3 2.28 90.5 Comparative Example 1 1.63 86.1 Comparative Example 2 1.54 84.3 Comparative Example 3 1.23 / Comparative Example 4 1.89 86.2 Comparative Example 5 2.16 90.6

[0099] Note: “ / ” indicates no self-healing capability.

[0100] It can be seen from Table 1 that the strength and self-healing ability of the ceramic fibers prepared by Examples 1 to 3 are better than those prepared by Comparative Examples 1 to 5. The reinforcing agent of Comparative Example 1 does not contain double bonds, and its tensile strength is reduced, indicating that the reinforcing agent containing carbon-carbon double bonds can undergo silylation reaction with the silicon-hydrogen bonds in polycarbosilane, so that the reinforcing agent and polycarbosilane can form a tighter cross-linked network, thereby improving the strength of the ceramic fiber. The reinforcing agent of Comparative Example 2 does not contain ester groups and carbon-carbon double bonds, and its tensile strength is reduced, indicating that the ester group, as an organic functional group, has a certain volume, which will improve the dispersibility of the reinforcing agent through the steric hindrance effect, thereby improving the strength of the ceramic fiber. Comparative Example 3 does not contain ester groups, disulfide bonds, carbon-carbon double bonds and imine groups, and the mechanical properties of the ceramic fiber are reduced, and it cannot be self-repaired. The self-healing properties and mechanical properties of Comparative Examples 4 and 5 are lower than those of Example 1 and Example 3, respectively, indicating that adding too much or too little reinforcing agent will affect the strength of the ceramic fiber, and adding too little will affect the self-healing properties of the ceramic fiber.

[0101] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0102] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing high-strength ceramic fiber, characterized in that: The following steps are involved: S1: adding polycarbosilane to anhydrous xylene, dissolving at 160-200°C, then adding a reinforcing agent, reacting at 160-200°C for 8-24h, cooling, distilling at normal pressure and distilling at reduced pressure to obtain modified polycarbosilane, wherein the reinforcing agent is prepared by condensation reaction of a self-repairing monomer and aldehyde-modified multi-walled carbon nanotubes, and the self-repairing monomer contains an imino group, a disulfide bond, an ester group, and a carbon-carbon double bond; S2: placing the modified polycarbosilane in a melt spinning cylinder, heating it to a molten state under an inert atmosphere, and performing a degassing treatment; then pressurizing it to 3 MPa, and the melt flows through a filter screen and a spinneret to obtain a silicon carbide fiber bundle; S3: placing the silicon carbide fiber bundle in a sintering furnace, passing nitrogen, heating and heating, and obtaining high-strength ceramic fibers after cooling in the furnace.

2. The method for preparing a high-strength ceramic fiber according to claim 1, characterized in that: In step S1, the amount ratio of polycarbosilane, anhydrous xylene and reinforcing agent is 100g:150mL:0.2-0.6g; the specific steps of atmospheric distillation and reduced pressure distillation are atmospheric distillation at 170-200°C under nitrogen atmosphere protection until no distillate is precipitated, and reduced pressure distillation at 300-350°C until no distillate is precipitated.

3. The method for preparing a high-strength ceramic fiber according to claim 1, characterized in that: In step S2, the inert gas is nitrogen or argon.

4. The method for preparing a high-strength ceramic fiber according to claim 1, characterized in that: In step S3, the temperature is raised to 500-550°C at a rate of 100-200°C / h and kept at this temperature for 2-4h; then the temperature is raised to 1000°C at a rate of 100-200°C / h and kept at this temperature for 4-6h; then the temperature is raised to 1300°C at a rate of 500-600°C / h, kept at this temperature for 0.5-1h, and cooled with the furnace; the flow rate of nitrogen is 100-200mL / min.

5. The method for preparing a high-strength ceramic fiber according to claim 1, characterized in that: The preparation method of the enhancer is: The self-repairing monomer and the aldehyde-modified multi-walled carbon nanotubes are added into anhydrous ethanol, reacted at 20-30° C. for 20-30 minutes, filtered and dried to obtain the enhancer.

6. The method for preparing high-strength ceramic fiber according to claim 5, characterized in that: The usage ratio of the self-repairing monomer, the aldehyde-modified multi-walled carbon nanotubes and the anhydrous ethanol is 3-6 g: 160 g: 1-1.2 L.

7. The method for preparing high-strength ceramic fiber according to claim 5, characterized in that: The preparation method of the self-repairing monomer is as follows: Add cystine, propylene alcohol, p-toluenesulfonic acid and toluene into a reaction bottle and stir; heat to 112°C, keep reflux for 3 hours, cool to -5 to 5°C in a water bath, keep warm for 1 hour; filter, wash with frozen toluene, and dry to obtain a self-repairing monomer.

8. The method for preparing high-strength ceramic fiber according to claim 7, characterized in that: The usage ratio of cystine, allyl alcohol, p-toluenesulfonic acid and toluene is 24g:14mL:2-4g:500-700mL.

9. The method for preparing high-strength ceramic fiber according to claim 5, characterized in that: The preparation method of aldehyde-modified multi-walled carbon nanotubes is as follows: The aminated multi-walled carbon nanotubes are added into a dialdehyde aqueous solution, stirred at room temperature for 6-8 hours, washed with deionized water, centrifuged and dried to obtain the aldehyde-aminated carbon nanotubes.

10. The method for preparing high-strength ceramic fiber according to claim 9, characterized in that: The molar ratio of the amino-modified multi-walled carbon nanotubes to the dialdehyde is 1-3:1; the dialdehyde is any one of glutaraldehyde and hexanedialdehyde.

Citation Information

Patent Citations

  • Method for preparing flexible silicon carbide / carbon nanotube composite fiber membranes by electrospinning

    CN106930004B

Cited By

  • Self-repairing ceramic fiber composite material, preparation method and application

    CN121556273A